Kinerja Keuangan Provinsi Kepulauan Bangka Belitung Ditinjau dari Derajat Kemandirian, Ketergantungan, dan Desentralisasi Fiskal - Nizwan Zukhri (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2020)
Bangka Belitung Islands is a province that was born in the era of regional autonomy. This province is demanded to be able to manage finances well to achieve regional independence. This paper aims to analyze the degree of independence, degree of dependency, and degree of fiscal decentralization of the Bangka Belitung Islands Province. The data used is the realization data of the Bangka Belitung Islands Province Regional Budget for the 2016-2018 fiscal year. This study uses a quantitative descriptive analysis method based on local government financial ratios in the form of independence ratios, dependency ratios, and fiscal decentralization ratios. The results showed that from the aspect of independence, the financial capability of the Bangka Belitung Islands Province was in the low category (46.09-49.83 percent) with a consultative relationship pattern. Based on the degree of regional dependency in the very high category (61.05-68.41 percent), whereas in terms of the degree of fiscal decentralization, the financial capability of the Bangka Belitung Islands Province is in the moderate-sufficient category (29.47-33.26 percent)